Pengaruh Budaya Organisasi, Work-Life Balance Dan Karakteristik Individu Terhadap Kepuasan Kerja Karyawan PT Abadikurnia Citrarasa di Surabaya - Ari Kuncoro Bagus Tawakal; M. Sihab Ridwan (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
In today's human resource management, increasing employee satisfaction is an important focus for companies. By paying attention to employee job satisfaction, namely by understanding and meeting employee needs, companies tend to have higher productivity and better employee retention. The purpose of this research is to analyze the significant influence of organizational culture, work-life balance and individual characteristics simultaneously on the employee job satisfaction of PT Abadikurnia Citrarasa in Surabaya. This research uses a quantitative approach using multiple regression analysis because the data used is in the form of a questionnaire with a total of 72 respondents. The research results showed that partially organizational culture, work-life balance and individual characteristics have a significant effect on employee job satisfaction at PT Abadikurnia Citrarasa. Simultaneously, organizational culture, work-life balance and individual characteristics have a significant effect on employee job satisfaction at PT Abadikurnia citrarasa in Surabaya.